(untitled) (Malay Literature, 2016)
Human issues are the dominant subjects in literary works because the human element and humanity are related in complex ways. This complexity is due to different cultural practices according to one’s country, ethnicity, religion and belief, which in turn shape one’s way of life, personality and character. Literature, on the whole, attempts to reflect the differences, uniqueness and complexities of people’s lives. Humanity, however, is a universal value that has a meaningful impact on the lives of people, which can be gleaned from reading literary works. This universal value can be discerned in animal fables, which are one branch of folk tales. Animal fables reflect human actions through animal characters. Ancient storytellers used such characters and characterizations as subtle and interesting expressions of humanity. Conflicts between characters demonstrate phenomena that really take place in human life. Issues such as leadership, and conflict and resolution are presented in a light, casual and comedic style. The comedic element Clear thinking filters the comedic element and provides knowledge, especially concerning natural phenomena. This article discusses several fables from the Hikayat Pelandok Jenaka that deal with conflicts within the community and their methods of resolution in order to reflect the knowledge of the Malay community of the past. Keywords: animal fable, reflections of Malay knowledge, Hikayat Pelandok Jenaka, conflict resolution